2021
DOI: 10.1093/nar/gkab135
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro reconstituted U1 snRNP allows the study of the disordered regions of the particle and the interactions with proteins and ligands

Abstract: U1 small nuclear ribonucleoparticle (U1 snRNP) plays a central role during RNA processing. Previous structures of U1 snRNP revealed how the ribonucleoparticle is organized and recognizes the pre-mRNA substrate at the exon–intron junction. As with many other ribonucleoparticles involved in RNA metabolism, U1 snRNP contains extensions made of low complexity sequences. Here, we developed a protocol to reconstitute U1 snRNP in vitro using mostly full-length components in order to perform liquid-state NMR spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 77 publications
0
18
0
Order By: Relevance
“…4A). U1 snRNP was reconstituted using recombinant components (21), and SF3A1-UBL was added before ultraviolet (UV) irradiation to induce protein-RNA cross-linking. The detection of all U1 snRNP proteins and protein-RNA cross-links for U1-70K and SmD2 fit well with the U1 snRNP structure and confirmed the correct reconstitution of the particle (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4A). U1 snRNP was reconstituted using recombinant components (21), and SF3A1-UBL was added before ultraviolet (UV) irradiation to induce protein-RNA cross-linking. The detection of all U1 snRNP proteins and protein-RNA cross-links for U1-70K and SmD2 fit well with the U1 snRNP structure and confirmed the correct reconstitution of the particle (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PTBP1-RRM1 could prevent the contacts of SF3A1 to the UUCG tetraloop and the correct positioning of the UBL core and the carboxyl-terminal tail. Additionally, PTBP1-RRM2, which has also been shown to bind U1-SL4, could increase the affinity of PTBP1 for U1-SL4 and might contribute to the steric hindrance of SF3A1-UBL binding (13,21,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results so far have shown that SRSF1 forms a heterodimer with U1 snRNP and is recruited by it to 5′SSs. To test whether the interaction between U1 snRNP and SRSF1 could be direct, we titrated 13 C ILV‐labelled SRSF1∆RS with in vitro reconstituted U1 snRNP using NMR spectroscopy (Fig 5A ), as we did previously for other splicing factors (Campagne et al , 2019 , 2021 ; Jutzi et al , 2020 ). SRSF1∆RS lacks the RS domain (amino acids 198–248) and is more soluble than the full‐length protein.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the cat RAPID online database predicted that circIL4R has the potential to bind with several proteins, such as SRSF9 and PTBP1. Previous studies have reported that these two proteins were involved in alternative splicing [ 57 , 58 ]. Whether circIL4R could regulate the alternative splicing via binding with SRSF9 or PTBP1 need further investigation.…”
Section: Discussionmentioning
confidence: 99%